Off‐label prescribing of targeted anticancer therapy at a large pediatric cancer center. (4th August 2020) - Lim, Mir; Shulman, David S.; Roberts, Holly; Li, Anran; Clymer, Jessica; Bona, Kira; Al‐Sayegh, Hasan; Ma, Clement; DuBois, Steven G.
Abstract: Background: Off‐label drug prescribing is common in pediatric clinical medicine, though the extent and impact of this practice in pediatric oncology has not yet been characterized. Methods: We completed a retrospective single‐institution cohort study evaluating prevalence, characteristics, and clinical outcomes of off‐label prescribing of 108 FDA‐approved targeted anticancer drugs in patients < 30 years old treated for cancer from 2007 to 2017. Dosing strategies were adjusted for body size and compared to FDA‐approved adult dosing regimen. A composite toxicity endpoint was defined as a patient having unplanned clinic visits, emergency department visits, or unplanned hospital admissions that were at least possibly related to the off‐label treatment. Results: The overall prevalence of off‐label use of targeted therapies was 9.2% (n = 374 patients). The prevalence increased significantly over the study period ( P < .0001). Patients treated off‐label were more likely to have neuro‐oncology diagnoses compared to patients not treated off‐label (46% vs 29%; P < .0001). Of the 108 potential agents, 38 (35%) were used by at least one patient. The median starting dose was below the FDA‐approved normalized dose for 44.4% of agents. Fifteen percent of patients had a complete response while receiving off‐label therapy, 38% experienced toxicity as defined, and 13% discontinued off‐label therapy due to toxicity. Conclusions: In this real‐world evaluation of prescribing at a large pediatric cancer center, off‐label prescribing of FDA‐approved targeted therapies was common, increasing in prevalence, encompassed a broad sample of targeted agents, and was tolerable. Clinicians commonly start dosing below the equivalent FDA‐approved dose. Abstract : Off‐label prescribing patterns and outcomes with targeted anticancer agents have not been previously described in pediatric oncology. In this analysis from a large pediatric cancer center, off‐label prescribing of FDA‐approved targeted therapies was common, increasing, encompassed a broad sample of targeted agents, and was tolerable.